Research of the Social Methods of a Project Team Formation and Its Complementarity. Example in Tourism Industry - MENDIGALIEV, Kairzhan; TSEKHOVOY, Alexey; BASSHIEVA, Zhangul; KUDAIBERGENOV, Nuradin; TOKAREVA, Yelena (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.10.8(40).16, 2020)
In the conditions of the existing competition in the market of innovative products, the requirements for personnel entrusted with the development of a new product or other type of activity are increasing. The need to have effective workers is dictated by the necessity to be the first to present a new product in the market, accordingly, the team working on a specific task should work efficiently, without any loss of time. Eventually, this brings up the question of how can you form an effective team? This article analyzes the concept and types of an effective team, the signs and characteristics of an effective work team, it pays attention to the managerial and organizational need for an effective team, and the stages of forming an effective team. Analysis of the concepts and methods of personnel management and their applicability to assess the performance of the project team will allow practitioners to more effectively form a project team taking into account interpersonal relations. The formulation of the task of forming a project team considering interpersonal relations of employees is shaped. To assess the optimality of the composition of the team a criterion characterizing the contribution of employees to group interaction is proposed. The methodological role of the principles of complementarity and its place in modern economics is analyzed.